2020
DOI: 10.1051/cocv/2019048
|View full text |Cite
|
Sign up to set email alerts
|

On a two-phase Serrin-type problem and its numerical computation

Abstract: We consider an overdetermined problem of Serrin-type with respect to an operator in divergence form with piecewise constant coefficients. We give sufficient condition for unique solvability near radially symmetric configurations by means of a perturbation argument relying on shape derivatives and the implicit function theorem. This problem is also treated numerically, by means of a steepest descent algorithm based on a Kohn-Vogelius functional.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…Proof. Since the eigenvalues of (4.2) have been computed in [CY1], in what follows we only need to check that the right-hand side in (4.2) vanishes if and only if k = 0. Furthermore, since N (Y 0,i ) = 0 by construction, it will suffice to show that N (Y k,i ) = 0 for k ∈ N. To this end, let ϕ denote the numerator in the right-hand side of (4.2), that is…”
Section: The Two-phase Dirichlet-to-neumann Mapmentioning
confidence: 99%
See 1 more Smart Citation
“…Proof. Since the eigenvalues of (4.2) have been computed in [CY1], in what follows we only need to check that the right-hand side in (4.2) vanishes if and only if k = 0. Furthermore, since N (Y 0,i ) = 0 by construction, it will suffice to show that N (Y k,i ) = 0 for k ∈ N. To this end, let ϕ denote the numerator in the right-hand side of (4.2), that is…”
Section: The Two-phase Dirichlet-to-neumann Mapmentioning
confidence: 99%
“…By the method of separation of variables, it can be shown that the spherical harmonics form an orthonormal basis of eigenfunctions of N in L 2 (∂Ω 2 ). The eigenvalues of N have been computed in [CY1].…”
Section: The Two-phase Dirichlet-to-neumann Mapmentioning
confidence: 99%